AVALIAÇÃO DE ÍNDICES DE COMPETIÇÃO NA MODELAGEM DO INCREMENTO EM DIÂMETRO DE ESPÉCIES ARBÓREAS EM FLORESTA OMBRÓFILA MISTA - RAMOS, LARISSA DE OLIVEIRA (2022)
This study aimed to evaluate the dynamics and distance-dependent and independent competition indices and its effect on modeling the periodic increment in diameter of five tree species in Mixed Ombrophilous Forest. The data for this study came from permanent plots installed and monitored every three years in the period 2002-2017 in the Irati National Forest (FLONA de Irati), Paraná state, Brazil. The data from the six measurements of the experiment were analyzed in order to describe the floristic composition of the forest and its dynamics (diametric distribution, increment, mortality and ingrowth). Ten distance-dependent and independent competition indices were evaluated, based on the Spearman correlation coefficient between each index and the annual periodic increment in diameter in the study period (15 years), evaluating the selection radius of neighboring competitors in the competition indices distance dependent. Individual tree models were also developed to estimate the annual periodic increase in diameter of each species and for the forest with four different approaches, depending on the competition indices that were tested, by the "stepwise" procedure. In 2002 there were a total of 580.8 trees ha-1 in the forest distributed in 113 species and 42 families, and in 2017 there were 588.7 trees ha-1 divided into 126 species and 45 families. In 15 years of monitoring, the forest showed an average increase in diameter of 0.24 cm.year-1. Regarding the basal area, the forest increased from 28.68 to 32.66 m² ha-1, that is, an average of 0.245 m² ha-1 year-1. The forest had an average mortality rate of 1.59% per year and entry rate was 1.68% per year. A. angustifolia, O. porosa and C. fissilis presented the most expressive diameter increment rates. In general, all distance-independent indices evaluated in this study showed good correlation with the growth of individual trees, with emphasis on the Stage, Corona and Ferrara, Glover and Holl, and Lorimer indices. Distance-dependent competition indices showed better correlations with the annual periodic increment in diameter using radii of 10, 15, 17 and 20 m. The models built to estimate the (IPAd) calculated based on the average of each monitoring period of the plots (3 years), for the forest (General) and for each species, inserting the DBHinterm provided superior estimates than the other built models, however, its practical application becomes difficult. This study contributes with subsidies for the inclusion of competition indices in increment models in the context of individual tree-level modeling in Mixed Ombrophilous Forest.